Diary of a wimpy kid : the third wheel - Kinney, Jeff. (New York : Amulet Books, 2014)
A Valentine's Day dance at Greg's middle school has turned his world upside down until an unexpected twist gives Greg a partner for the dance and leaves his best friend Rowley the odd man out.
Keywords: Schools -- Fiction; Valentine's Day. -- Fiction; Humorous stories